Intelligent engineering management of prefabricated building based on BIM Technology - Feng, Jing; zhang, Zhiying; Xu, Yuequn; Zhang, Aiju (Informatica, 2022)
In order to solve the problem that China's construction industry has adopted the more traditional extensive construction mode for a long time, and falling from height has the largest number of accidents among various types of safety accidents in the construction industry. 277 accidents of falling from height, accounting for 54% of the total; There were 72 collapse accidents, ranking second among all types of safety accidents in the construction industry. This paper puts forward a new mode of fine construction management based on BIM, and discusses the application measures and benefits of BIM Technology in fine management from four aspects of quality management, schedule control, cost management and safety management. It is demonstrated that BIM Technology has brought good economic and social effects to fine management.